Effects of Acupuncture on Alzheimer's Disease in Animal-Based Research. (27th September 2017) - Park, Sunjung; Lee, Jun-Hwan; Yang, Eun Jin
Abstract : Alzheimer's disease (AD) is a chronic neurodegenerative disease characterized by the accumulation of amyloid beta (A β ) plaques, neurofibrillary tangles, and severe functional deficits in the brain. The pathogenesis and treatment of AD remain topics of investigation and significant global socioeconomic issues. The effect of complementary medicine has been investigated in managing AD. Acupuncture, a form of therapy practiced for more than 3000 years, has shown positive effects on several neurological disorders including AD. Animal studies have evaluated the specific utility and neuropathological mechanisms addressed by acupoint manipulation; however, no study has summarized the relationships among different acupoints and their therapeutic effects in the context of AD. Therefore, we reviewed the effects of acupuncture at different acupoints in animal models of AD. In general, acupuncture produced therapeutic benefits in rodent models of AD. Studies demonstrate the utility of GV20 as a valuable acupoint for electroacupuncture and manual acupuncture. GV20 stimulation suppresses A β generation, improves glucose metabolism, and attenuates neuropathological features in various disease models. However, a lack of sufficient evidence in preclinical and clinical studies makes these results controversial. Additional studies are required to confirm the exact utility of specific acupoints in clinically managing AD.